Goal orientation profile differences on perceived motivational climate, perceived peer relationships, and motivation-related responses of youth athletes - Smith, A. L.; Balaguer, I.; Duda, J. L. (Journal of Sports Sciences, 2006)
The aims of this study were twofold: (a) to determine if dispositional achievement goal orientation profiles that are reported in the literature would be observed in a sample of youth athletes, and (b) to examine potential achievement goal orientation profile differences on perceptions of the motivational climate, perceptions of peer relationships, and motivation-related responses. Male soccer players (n = 223) aged 9-12 years (mean = 10.9, s = 0.6) completed a multi-section questionnaire containing assessments of dispositional goal (task, ego) orientations, the perceived task- and ego-involving features of the motivational climate, perceived peer acceptance and friendship quality (positive friendship quality, conflict), perceived ability, soccer enjoyment, and satisfaction with one's performance and the team. Four profiles were observed that closely matched those observed by Hodge and Petlichkoff (2000), though in the present study a lower proportion of participants exhibited achievement goal profiles consisting of relatively high ego orientation. Achievement goal profile differences were found for all variables except positive friendship quality, with a general trend for those reporting relatively lower task goal orientation to exhibit less adaptive responses. Overall, the findings support achievement goal frameworks (e.g. Nicholls, 1989) and suggest that further examination of dispositional achievement goals may afford a deeper understanding of social relationships and motivational processes in youth sport.